A Study on the Dual-Role Conflict and Integration of Design Managers As “Creative Advocate” and “Project Constraint Controller” - Zhou, Weiping (International Journal of Multidisciplinary Research, 2025)
The green transition in the architecture and interior design industry is being put under pressure by the global trend of pursuing Dual Carbon goals and ESG principles. The key players in this process are design managers. They have been struggling with a dilemma between dual roles: creative vision protection and project constraint control. Sustainable development has exacerbated this inherent conflict. It becomes a powerful new agenda, tightening even further the traditional tension between creativity and commercial reality. This paper examines the new features of this conflict in the modern context. We believe that effective managers must not make binary decisions but become efficient translators and coordinators. Their main objective is to convert sustainable ideas into feasible designs and budgets which can be accepted by all stakeholders. This article offers fresh perspectives and practical methods for design managers who find themselves in this new age.